THE EFFECT OF PICTURE AND PICTURE LEARNING MODELS ON ELEMENTARY SCHOOL STUDENT LEARNING OUTCOMES - Zulfadli Zulfadli; Mardhatillah Mardhatillah; Agus Kistian (Jurnal Ilmiah Teunuleh, 2020)
This study aims to find out the influence of picture and picture learning models on the learning outcomes of grade II students at SD Negeri 1 Simpang 4 on the theme of clean and healthy living. The approach used in this research is a quantitative approach with the type of research used is quasi experimentation. The sample in this study consisted of 42 people consisting of 21 people of class IIA and 21 people of class IIB. Data collection techniques used are observation, test, validation, and documentation. The data analysis technique used is the T-test analysis. Based on the results of the study, it was found that the average posttest value of students' learning outcomes in the experimental class (II-B) of SD Negeri I Simpang Peut Nagan Raya regency was 76.19, while the average posttest score of students in the control class (II-B) of SD Negeri I Simpang Peut Nagan Raya regency was 63.33. This is proven by the results of statistical data analysis "T-Test Test" that obtained thitung value (3,339) > ttabel (1,724). This proves that hypotheses are accepted. Thus, it can be concluded that the picture and picture learning model affects students' learning outcomes on the theme of clean and healthy living in grade II of SD Negeri 1 Simpang Peut.